Atomizing core, atomizer and electronic atomizing device

By introducing a transition layer of inorganic material components into the atomization core of the electronic atomization device, the problem of short life and easy dry burning in the prior art is solved, and a longer service life and more efficient fog are achieved. .

CN119488171APending Publication Date: 2025-02-21SMOORE INTERNATIONAL HOLDINGS LIMITED
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311040870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-17
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The atomization core in existing electronic atomization devices has a short life, which is prone to problems such as dry burning.

Method used

An atomized core is used including a porous substrate, a heating element and a transition layer bonded between the porous substrate and the heating element. The transition layer contains an inorganic material component, and the heat generator and the porous matrix are bonded and fixed through the transition layer.

Benefits of technology

The service life of the atomized core is improved, problems such as dry burning are avoided, and uniform heat transfer of the heating body and efficient liquid conduction of the porous matrix are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488171A_ABST
    Figure CN119488171A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic atomization devices, in particular to an atomization core, an atomizer and an electronic atomization device. The invention provides an atomizing core. The atomizing core comprises a porous base body, a heating body and a transition layer bonded between the porous base body and the heating body. The transition layer contains an inorganic material component. The atomizing core provided by the invention has excellent service life, and the problems of dry burning and the like are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic atomization devices, and in particular to an atomization core, an atomizer and an electronic atomization device. Background Art

[0002] Existing electronic atomization devices usually use an atomizer core to atomize the atomization medium. Among them, the atomizer core usually includes a porous matrix and a heating element. The existing technology usually uses porous ceramics as the porous matrix and conductive metal materials as the heating element. The conductive metal heating element usually needs to be fixed by embedding it in the porous ceramic matrix. The atomizer core obtained in this way has a short lifespan and is prone to dry burning. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the atomizer core in the prior art, such as short service life and easy dry burning, and further provide an atomizer core, an atomizer and an electronic atomization device.

[0004] In order to achieve the above object, the present invention adopts the following technical scheme:

[0005] An atomizer core, comprising a porous matrix, a heating element, and a transition layer bonded between the porous matrix and the heating element;

[0006] The transition layer contains inorganic material components.

[0007] Preferably, the transition layer contains a glass phase component;

[0008] and / or, the porous matrix contains glass phase components and / or ceramic phase components;

[0009] Preferably, the softening point temperature of the glass in the transition layer is 400°C-1100°C.

[0010] Preferably, the content of inorganic material components in the transition layer is greater than 80wt%;

[0011] Preferably, the content of inorganic material components in the transition layer is greater than 90wt%;

[0012] Preferably, the content of the inorganic material component in the transition layer is 100 wt %.

[0013] Preferably, the transition layer at least partially fills and / or covers the porous matrix;

[0014] Preferably, the transition layer at least partially fills and / or covers the area where the heating element contacts the porous matrix;

[0015] Preferably, the area on the porous substrate that is not in contact with the heating element is at least partially not filled and / or covered by the transition layer.

[0016] Preferably, the transition layer fills part of the pores of the porous matrix to form an embedded structure;

[0017] And / or, the transition layer is a dense structure.

[0018] Preferably, the thickness of the transition layer is 20-200 μm;

[0019] Preferably, the transition layer has a thickness of 100-160 μm.

[0020] Preferably, the composition of the transition layer includes aluminosilicate glass and / or barium silicate glass;

[0021] And / or, the composition of the porous matrix includes soda-lime silicate glass and / or borosilicate glass.

[0022] Preferably, the porosity of the porous matrix is ​​20%-90%;

[0023] Preferably, the porosity of the porous matrix is ​​40-80%.

[0024] Preferably, the average pore size of the porous matrix is ​​10-300 μm;

[0025] Preferably, the average pore size of the porous matrix is ​​15-60 μm;

[0026] Preferably, the average pore size of the porous matrix is ​​20-50 μm.

[0027] Preferably, the pores of the porous matrix include at least one of ordered straight through pores, ordered curved through pores or disordered pores.

[0028] Preferably, the heating element is a metal mesh or a metal sheet;

[0029] And / or, the material of the heating element is selected from at least one of an iron-based alloy material and a nickel-based alloy material;

[0030] Preferably, the heating element is selected from at least one of stainless steel and iron-chromium-aluminum.

[0031] Preferably, the shape of the heating element is rhombus or honeycomb.

[0032] Preferably, the thickness of the heating element is 20-200 μm;

[0033] Preferably, the heating element has a thickness of 50-120 μm.

[0034] Preferably, at least part of the surface of the heating element has a micro-nano structure;

[0035] Preferably, the surface roughness Ra of the heating element with micro-nano structure is 100-300nm.

[0036] Preferably, the ratio of the area of ​​the porous matrix filled and / or covered by the transition layer to the area of ​​the porous matrix covered by the heating element is (0.8-1.2):1;

[0037] Preferably, the ratio of the area of ​​the porous matrix filled and / or covered by the transition layer to the area of ​​the porous matrix covered by the heating element is 1:1.

[0038] The present invention provides an atomizer, comprising the atomizer core as described above.

[0039] The present invention also provides an electronic atomization device, comprising the atomizer and power supply assembly as described above.

[0040] Beneficial effects of the present invention:

[0041] The atomizer core provided by the present invention comprises a porous matrix, a heating element, and a transition layer bonded between the porous matrix and the heating element; the transition layer contains an inorganic material component. The transition layer is arranged between the heating element and the porous matrix, and the two are bonded and fixed by the transition layer. The obtained atomizer core has an excellent service life and avoids problems such as dry burning. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 A schematic cross-sectional view of an atomizer core provided in Example 1 of the present invention;

[0044] Figure 2 SEM image of the cross section of the atomizer core provided in Example 1 of the present invention;

[0045] Figure 3 A schematic diagram of the shape of the heating element on the atomizer core provided by the present invention;

[0046] Figure 4 A physical picture of the atomizer core of Example 1 of the present invention;

[0047] Figure 5 SEM image of the atomizing surface of the atomizing core of Example 1 of the present invention;

[0048] Figure 6Comparison of the temperature rise curves of the heating element during the temperature field test of each sample in Example 1 of the present invention;

[0049] Figure 7 Infrared temperature field area distribution diagram of each sample temperature field test in Example 1 of the present invention;

[0050] Explanation of the reference numerals: 1-porous matrix, 2-heat generating element, 3-transition layer. DETAILED DESCRIPTION

[0051] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0052] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0053] Existing electronic atomization devices usually use an atomization core to atomize the atomization medium. Among them, the atomization core usually includes a porous matrix and a heating element. The prior art usually uses porous ceramics as the porous matrix and conductive metal materials as the heating element. The conductive metal heating element usually needs to be fixed by embedding it in a porous ceramic matrix. The inventors have found that when the above method is used to fix heating elements such as heating wires, heating nets or heating sheets, only a few points embedded in the porous matrix are in close contact with the matrix. Most of the other parts of the heating element are not in close contact with the porous matrix, and there is a certain gap between the porous matrix and the heating element. This inaccurate contact method will further cause the following problems: First, the thermal resistance between the heating element and the porous matrix is ​​large. Due to the low thermal conductivity of air and the atomization medium, the heat of the heating element is concentrated on the heating element. It is not easy to transfer and disperse the heat to the entire atomization surface, which is easy to cause local high temperature, and then cause dry burning; at the same time, local high temperature also accelerates the formation of carbon deposits, affecting the taste and service life of the atomization core. Second, since most of the heating element is not in close contact with the porous matrix, its deformation is not constrained. Under thermal shock, the deformation of each part of the heating element is not consistent, which can easily cause excessive local deformation, resulting in warping, fracture, etc., affecting the service life. Third, the consistency of the gap between the heating element and the porous matrix is ​​poor; due to its sintering and curing process, the porous matrix has a certain shrinkage rate, resulting in poor consistency of the gap, and excessive gaps cause insufficient liquid supply to the heating element, causing problems such as dry burning; in particular, poor consistency causes large differences in smoke, resulting in poor taste consistency, affecting the consumer experience. Therefore, the atomizer core obtained in this way has a short lifespan and is prone to problems such as dry burning.

[0054] Based on the above analysis, the present invention provides an atomizer core to solve and improve the above specific technical problems. Figure 1As shown, the atomizing core includes a porous matrix 1, a heating element 2, and a transition layer 3 bonded between the porous matrix and the heating element; the transition layer contains an inorganic material component. For the convenience of description, the present invention refers to a surface of the porous matrix provided with the transition layer and the heating element as an atomizing surface, and the liquid atomizing medium is guided to the atomizing surface for atomization under the capillary action; the surface opposite to the atomizing surface is called a liquid absorbing surface, which is used to absorb the liquid atomizing medium, and the distance between the atomizing surface and the liquid absorbing surface is the thickness of the porous matrix. Since a transition layer is provided between the heating element and the porous matrix, and the two are bonded and fixed by the transition layer, there is no gap between the two. At the same time, since the transition layer contains inorganic material components, its thermal conductivity is much greater than that of air. Therefore, on the first hand, the effect of quickly and efficiently directing the heat on the heating element to the atomization surface of the porous matrix is ​​achieved, and the heat is transferred and dispersed to the entire atomization surface, avoiding local high temperature and dry burning; on the second hand, the transition layer bonds the heating element so that its deformation under thermal shock is subject to certain constraints. At the same time, since the temperature of the atomization surface is more uniform, the deformation of each part of the heating element tends to be consistent, avoiding warping, fracture, etc., and extending its service life; on the third hand, there is no gap between the porous matrix and the heating element in the atomization core of the present invention, so the oil film on the atomization surface can be more evenly distributed, and the liquid supply to the heating element is more efficient, avoiding insufficient liquid supply. Therefore, the atomization core of the present invention solves the above-mentioned problems of the prior art at the same time, improves the service life of the atomization core, and avoids problems such as dry burning.

[0055] In some optional embodiments, the content of inorganic material components in the transition layer is greater than 80wt%; preferably, the content of inorganic material components in the transition layer is greater than 90wt%; particularly preferably, the content of inorganic material components in the transition layer is 100wt%. It can be understood that since inorganic material systems generally have higher thermal conductivity, thermal stability and safety, the higher the content of inorganic material components in the transition layer, the better the effect.

[0056] In some optional embodiments, the transition layer contains a glass phase component. It is understood that glass is an amorphous inorganic non-metallic material, and the glass phase is a solid phase having the above-mentioned amorphous inorganic non-metallic characteristics. The glass phase in the present invention can be sintered by a slurry containing glass powder. The advantage of the glass phase is that during the sintering and molding process, it has a certain fluidity and bonding effect, which is conducive to achieving good contact and bonding with the contact surface of the heating element, and better filling the gap between the heating element and the porous matrix.

[0057] like Figure 1 and Figure 2 As shown, in some optional embodiments, the transition layer is a dense structure. The dense structure has a higher thermal conductivity and better mechanical properties, and can enhance the bonding strength between the heating element and the transition layer.

[0058] In some optional embodiments, the transition layer at least partially fills and / or covers the porous matrix. Figure 2 As shown, the transition layer can fill part of the pores of the porous matrix to form an embedded structure. The transition layer is used to bond and fix the metal heating element to the surface of the porous matrix. The embedded structure formed by the transition layer and the porous matrix can effectively improve the bonding strength between the two to avoid warping of the heating element and improve the service life. Based on the embedded structure, it is almost impossible for the transition layer to be separated from the porous matrix without destroying the porous matrix. Furthermore, the transition layer has no pores and is densely filled between the heating element and the porous matrix, which also improves the thermal conductivity, quickly introduces heat into the porous matrix, and makes the atomization effect good, reducing the probability of dry burning. Furthermore, during sintering and curing, the porous matrix and the transition layer embedded in the porous matrix are embedded due to a certain fluidity, the bonding strength is further enhanced, and the service life is further guaranteed. Specifically, the transition layer can also cover the porous matrix. It is manifested in that part of the transition layer only covers the surface of the porous matrix, and the part of the transition layer does not penetrate into the pores for filling. The transition layer that has not penetrated into the pores can achieve the bonding and fixing of the porous matrix and the heating element alone, or it can cooperate with the transition layer filled in the pores to achieve the bonding and fixing of the porous matrix and the heating element together. It can be understood that the transition layer filling the porous matrix will reduce the porosity of the porous matrix in this area to a certain extent, and reduce the proportion of open pores in this area; thereby affecting the liquid conduction effect of this area. The transition layer covering the porous matrix will reduce the proportion of open pores in this area to a certain extent, and will also affect the liquid conduction effect of this area.

[0059] In some optional embodiments, the transition layer at least partially fills and / or covers the area where the heating element contacts the porous matrix. A close combination of the heating element and the porous matrix is ​​achieved. At the same time, it can be understood that the transition layer with a dense structure filled and / or covered in the porous matrix will reduce the porosity of the porous matrix and reduce the liquid conduction effect of this part. Therefore, the corresponding area filled only in the contact area between the heating element and the porous matrix can ensure the high liquid conduction effect of other parts of the porous matrix, that is, reduce the impact on the porosity and opening rate of the atomization surface. Therefore, in some optional embodiments, the area on the porous matrix that is not in contact with the heating element is at least partially not filled and / or covered by the transition layer to achieve a good liquid conduction effect; it can be understood that the more ideal situation is that in the planar direction of the atomization surface of the porous matrix, the transition layer fills and / or covers the porous matrix area corresponding to the heating element, while other areas are not filled and / or covered by the transition layer. Ideally, the ratio of the area of ​​the transition layer filled and / or covered porous matrix to the area of ​​the heating element covered porous matrix is ​​(0.8-1.2):1, within which both strength and liquid conduction effects are achieved; preferably, the ratio of the area of ​​the transition layer filled and / or covered porous matrix to the area of ​​the heating element covered porous matrix is ​​1:1. Figure 5As shown, in this embodiment, it can be seen that the porous matrix area outside the heating element has a good pore structure, and a good liquid conduction effect is achieved in this area.

[0060] In some optional embodiments, the thickness of the transition layer is 20-200 μm; preferably, the thickness of the transition layer is 100-160 μm. For example, the thickness of the transition layer can be selected to be 100 μm, 102 μm, 105 μm, 107 μm, 110 μm, 112 μm, 115 μm, 117 μm, 120 μm, 122 μm, 125 μm, 127 μm, 130 μm, 132 μm, 135 μm, 137 μm, 140 μm, 142 μm, 145 μm, 147 μm, 150 μm, 152 μm, 155 μm, 157 μm, 160 μm. The filling of the porous matrix by the transition layer in the thickness direction will also affect the liquid conduction in the thickness direction to a certain extent. Therefore, the thickness of the transition layer needs to be selected so as not to affect the normal heating and atomization function of the atomizer core and not to reduce the overall bonding strength. The above thickness range ensures good bonding strength and liquid conducting effect.

[0061] In some optional embodiments, the thickness of the transition layer may be non-uniform; the maximum thickness of the non-uniform transition layer is 60-200 μm. For example, the maximum thickness may be 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm. Since in some embodiments, the surface of the porous substrate is uneven, the thickness of the transition layer at the minimum thickness portion may be much smaller than the maximum thickness portion, for example, the minimum thickness of the transition layer may be 0.1-30 μm. Generally, the better the surface flatness of the porous substrate, the better the uniformity of the thickness of the transition layer.

[0062] In some optional embodiments, the raw material of the transition layer of the present invention uses glass powder, which is conventional glass powder in the art and can be obtained commercially. The softening point temperature of the glass in the transition layer is 400°C-1100°C; it can be understood that silicon dioxide is the main component of the transition layer, and other components of the transition layer include aluminum oxide, calcium oxide, barium oxide, zinc oxide, etc., which are used to adjust the softening point temperature of the glass to improve the sintering and curing temperature and the fluidity of the glass. It should be noted that the softening point temperature should not be too low, and it should at least be greater than the upper limit of the maximum temperature range in which the atomizer core can work; at the same time, the softening point temperature of the glass in the transition layer should not be too high, and it should at least be less than the molding temperature or the destruction temperature of the porous matrix to avoid affecting the structural stability of the porous matrix. Further, the components of the transition layer include aluminosilicate glass and / or barium silicate glass.

[0063] In some optional embodiments, the porosity of the porous matrix is ​​20%-90%. Preferably, the porosity of the porous matrix is ​​40-80%. For example, the porosity of the porous matrix can be selected to be 40%, 42%, 45%, 46%, 48%, 50%, 51%, 53%, 56%, 58%, 59%, 60%, 61%, 63%, 65%, 67%, 69%, 70%, 71%, 72%, 74%, 75%, 76%, 77%, 78%, 79%, 80%.

[0064] In some optional embodiments, the average pore size of the porous matrix is ​​10-300 μm. Preferably, the average pore size of the porous matrix is ​​15-60 μm. Preferably, the average pore size of the porous matrix is ​​20-50 μm. For example, it can be selected that the average pore size of the porous matrix is ​​20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, 40 μm, 41 μm, 42 μm, 43 μm, 45 μm, 46 μm, 47 μm, 48 μm, 49 μm, 50 μm.

[0065] In some optional embodiments, the pores of the porous matrix include at least one of ordered straight through pores, ordered tortuous through pores, or disordered pores.

[0066] In some optional embodiments, the porous matrix contains a glass phase component and / or a ceramic phase component. The present invention does not specifically limit the porous matrix. The porous matrix can be a ceramic porous matrix mainly composed of ceramic components, a glass porous matrix mainly composed of glass components, or a glass ceramic porous matrix. The porous matrix has a porous structure inside, and liquid conduction is achieved by capillary effect. The glass softening point temperature in the porous matrix is ​​600-1200°C; preferably, the porous matrix is ​​a glass ceramic porous matrix. Furthermore, the components of the glass ceramic porous matrix include soda-lime silicate glass and / or borosilicate glass.

[0067] In some optional embodiments, the transition layer and the porous matrix both contain glass phase components, and the components of the porous matrix and the transition layer match, which helps to improve the bonding strength, reduce warping, and increase the service life; at the same time, the similar components can make the porous matrix and the transition layer have basically the same expansion coefficient, which can increase the service life under the thermal shock of the atomizer core application.

[0068] In some optional embodiments, the raw material components of the porous matrix include glass powder, and further, the glass powder is composed of silicon oxide, boron oxide, sodium oxide, calcium oxide, and aluminum oxide.

[0069] In some optional embodiments, the porous matrix, the transition layer and the heating element are bonded together by sintering and curing. The sintering and curing temperature is 800-1100°C, and the sintering and curing time is 8-12 minutes. At this curing temperature, the softening point of glass is reached. Especially when both the porous matrix and the transition layer have a glass phase, the porous matrix and the transition layer can also produce good fluidity and fit together when sintered at a higher temperature. Therefore, the bonding strength between the porous matrix and the transition layer is further improved, warping is reduced, and the service life is increased.

[0070] The present invention does not specifically limit the specific preparation method of the porous matrix or the pore-forming method thereof. Typically and non-limitingly, in some optional embodiments, the preparation method of the porous matrix comprises the following steps:

[0071] 1) mixing raw glass bubbles with a binder, a lubricant and water and extruding the mixture to obtain a green body;

[0072] 2) subjecting the green body in step 1) to a first sintering, a second sintering and a third sintering to obtain a porous glass-ceramic matrix;

[0073] Optionally, in step 1), the binder may be an organic binder; specifically, the binder is selected from at least one of methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl methyl cellulose; the lubricant may be an aliphatic hydrocarbon lubricant, such as paraffin and metal stearate; specifically, the lubricant is sodium stearate.

[0074] Optionally, the pressure of the extrusion molding in step 1) is 1-30 bar. Most of the glass bubbles do not break during the extrusion molding process, and the single glass bubble maintains a complete spherical shape. Therefore, the extrusion molding pressure can be appropriately adjusted according to the compressive strength of the selected glass bubble.

[0075] Optionally, the first temperature of the first sintering in step 2) is at least 200° C., such as 300° C. to 400° C., and / or the first residence time is at least 1 minute, such as 1 to 10 hours. During the sintering process at this temperature, substances such as solvents and binders in the green body are removed.

[0076] Optionally, the second temperature of the second sintering is greater than 400°C and less than the softening point of the glass of the glass bubble; for example, 500°C, 600°C, 700°C, etc., and the second residence time is at least 1 minute, for example, 1 to 10 hours. The second temperature is higher than 400°C and lower than the softening point of the glass of the glass bubble. The purpose is to keep the original shape of the blank unchanged. At the same time, since the temperature is already higher than 400°C, the glass component in the glass bubble begins to undergo a phase change, and the disordered glass phase partially crystallizes into a crystalline phase within this temperature range. The glass bubble is transformed into a glass ceramic bubble or the proportion of the crystalline phase in the glass bubble begins to increase. At the same time, due to this transformation, some glass bubbles begin to break and have at least one opening. Therefore, the sintering time within this temperature range can be appropriately adjusted to adjust the crystallinity of the porous glass ceramic. It can be understood that the raw glass bubble itself can also contain a certain proportion of crystalline phases, which can shorten the sintering time in this process.

[0077] Optionally, the third temperature of the third sintering is greater than the softening point of the glass. Specifically, the softening point temperature of the glass is less than 900°C. The third residence time can be at least 1 minute, for example, 1 to 10 hours. At this temperature, the glass component has fluidity, so the adjacent glass-ceramic bubbles are directly bonded to each other, and the glass-ceramic bubbles are bonded to form a porous glass-ceramic matrix with an integrated structure; at the same time, because the glass-ceramic bubbles still have crystalline phase components, the crystalline phase components serve as a skeleton so that their morphology does not collapse and still maintains a basically complete morphology. In addition, the glass-ceramic bubbles further crack to form a large number of openings, which are interconnected to form pores, and the pores extend through the porous glass-ceramic matrix and reach the surface of the porous glass-ceramic matrix.

[0078] The third temperature is higher than the softening point of the glass of the glass bubble. The glass ceramic bubble is heated to at least the softening temperature of the amorphous glass, so that most of the glass ceramic bubbles are opened due to the expansion of the gas in the bubble, and the adjacent glass ceramic bubbles are sintered together by heating to form a bond. From the overall point of view, the bonded open glass ceramic bubbles form pores in the porous glass ceramic matrix, which can be used in atomizers and electronic atomization devices to effectively improve the atomization efficiency and liquid guiding effect.

[0079] In some optional embodiments, the mass ratio of glass bubbles to binder, lubricant and water is (100-200): (10-50): (1-10): (45-150).

[0080] In some optional embodiments, the glass component in the glass bubble may be soda-lime silicate glass, borosilicate glass or other glass. Specifically, the glass component may include Si: 40-44wt%, O: 45-52wt%, Na: 2-5wt%, Ca: 2-6wt%, Mg: 0.1-0.5wt%, Al: 0.1-0.5wt%, or may include: SiO2 74-85wt%, CaO 6.5-10wt%, B 2 O 3 5-9wt%, Al 2 O 3 0.4-2wt%, Fe 2 O 3 0.01-1wt%, Na 2 O 1-3wt%, K 2 O0.1-0.5wt%.

[0081] In some optional embodiments, step 1) further includes adding a pore former. Optionally, the pore former is selected from at least one of starch, polymethyl methacrylate (PMMA), polystyrene (PS), and graphite. Optionally, the average particle size of the pore former can range from 1 to 150 μm. It can be understood that the addition of the pore former can further improve the porosity of the porous glass ceramic matrix while ensuring the strength of the raw glass bubble.

[0082] In some optional embodiments, step 1) further includes a second inorganic material. The second inorganic material may be at least one of clay, talc, silica, and alumina. The melting point or softening point of the above materials is higher than the softening point of the glass in the glass bubble.

[0083] In some optional embodiments, the mass ratio of glass bubbles to binder, slip agent, water, pore former, and second inorganic material is (100-200): (10-50): (1-10): (45-150): (0-70): (0-9).

[0084] The porous matrix prepared by the above preparation method is a porous glass ceramic matrix (referred to as the first porous matrix), including a plurality of glass ceramic bubbles; wherein adjacent glass ceramic bubbles are directly bonded to each other by sintering; at least part of the glass ceramic bubbles have openings; the cavities in the glass ceramic bubbles with openings are interconnected through the openings to form pores, and the pores extend through the porous glass ceramic matrix and reach the surface of the porous glass ceramic matrix. In the present invention, the pores with disordered extension directions of such a pore structure are referred to as disordered pores. The pores of this porous matrix include disordered pores, and it is a glass ceramic porous matrix, that is, the porous matrix contains glass phase components and ceramic phase components. In the present invention, the porous matrix having the above structure is named the first porous matrix.

[0085] Typically, but not limiting, in some other optional embodiments, the method for preparing the porous matrix comprises the following steps:

[0086] 1) stacking ablative organic material screens to form a three-dimensional organic template;

[0087] 2) Filling the ceramic slurry into the three-dimensional organic template, drying, degreasing, and sintering to obtain the ceramic matrix.

[0088] Preferably, the method for preparing the ceramic slurry comprises the following steps: mixing silicon dioxide, potassium feldspar, an organic monomer, a cross-linking agent and water, adjusting the pH, and grinding to obtain the ceramic slurry.

[0089] Preferably, the three-dimensional organic template forms three-dimensional pores in the ceramic matrix after ablation.

[0090] Preferably, the material of the organic material screen is an organic polymer material; and / or,

[0091] The organic polymer material includes one of a polyamide material and a polyester material.

[0092] Preferably, the material of the organic material screen is selected from at least one of nylon and polyethylene terephthalate.

[0093] Preferably, the organic material mesh in step 1) is formed by alternately weaving organic material threads through warp and weft.

[0094] Optionally, the weaving method may be plain weaving, and the organic material thread may be woven by alternating 1 warp and 1 weft.

[0095] Preferably, the diameters of the warp and weft may be the same or different, and the diameter range is 10-200 microns.

[0096] Optionally, the diameter of the warp is 10-80 microns;

[0097] Optionally, the diameter of the weft is 10-150 microns.

[0098] Preferably, the spacing between adjacent warps is 20-300 microns, and the spacing between adjacent wefts is 20-300 microns;

[0099] Optionally, the spacing between adjacent warp threads is 20-150 microns, and the spacing between adjacent weft threads is 20-150 microns.

[0100] Preferably, the organic material screen further comprises the step of fixing it with an outer frame;

[0101] Optionally, the outer frame is a metal outer frame.

[0102] Preferably, the number of layers of the organic material screen after stacking in step 1) is 50-500, and the thickness after stacking is 2-10 mm. Optionally, there may be a certain distance between adjacent layers, for example, the distance between layers may be 10-100 microns.

[0103] Preferably, after stacking the organic material screens in step 1), the step further includes fixing the stacked screens with a clamp.

[0104] Preferably, the method for preparing the ceramic slurry in step 2) comprises the following steps: mixing ceramic powder, organic monomer, cross-linking agent and water, adjusting pH, and grinding to obtain the ceramic slurry.

[0105] Preferably, the mass ratio of the ceramic powder, the organic monomer, the cross-linking agent and water is (60-80): (2-5): (0.2-2): (15-40); and / or,

[0106] The organic monomer is acrylamide, and the cross-linking agent is N,N'-methylenebisacrylamide.

[0107] Preferably, the method for preparing the ceramic slurry further comprises the step of adding an initiator and a catalyst into the ceramic slurry.

[0108] Preferably, the mass ratio of the organic monomer, the initiator and the catalyst is (1-10):(0.1-1):(0.1-1);

[0109] The initiator is ammonium persulfate;

[0110] The catalyst is tetramethylethylenediamine.

[0111] Preferably, the ceramic powder comprises silicon dioxide and a sintering aid;

[0112] The mass ratio of the silicon dioxide to the sintering aid is (55-95):(5-30).

[0113] Preferably, the sintering aid is potassium feldspar.

[0114] Preferably, the grinding speed is 50-100 rpm, and the grinding time is 24-36 h; and / or,

[0115] The pH value of the ceramic slurry is adjusted to 8-10 during preparation; and / or,

[0116] The pH regulator is ammonia water or tetramethylammonium hydroxide;

[0117] Optionally, the grinding may be ball milling.

[0118] Optionally, the mass concentration of ammonia in the ammonia water is 5-39%.

[0119] Preferably, the drying temperature in step 2) is 25-60° C. and the drying time is 24-120 h; and / or,

[0120] In step 2), the degreasing temperature is 450-500° C. and the degreasing time is 1800-2400 min; and / or,

[0121] In step 2), the sintering temperature is 1150-1200° C., and the sintering time is 1200-1800 min.

[0122] The optional ambient humidity of the drying step is 30-80%. Ambient humidity refers to the relative humidity of the environment. Maintaining the ambient humidity at 30-80% is beneficial to preventing cracks from forming on the ceramic matrix during the drying process.

[0123] The above-mentioned method constructs a three-dimensional organic template, pours ceramic slurry, and degreases and sinters to form a dense ceramic (referred to as the second porous matrix) with an interconnected through-hole structure. The ceramic porous matrix has a longitudinal through-hole structure that vertically penetrates the upper and lower surfaces (liquid absorption surface and atomization surface) of the ceramic matrix, and a transverse curved through-hole structure connected to the longitudinal through-hole.

[0124] Similarly, in some other optional embodiments, the three-dimensional organic template in the above preparation process is replaced with an organic template extending in a two-dimensional direction, that is, a fiber template that only includes organic material threads that penetrate the upper and lower surfaces (liquid absorption surface and atomization surface) of the ceramic substrate. A ceramic porous substrate is prepared using a basically similar scheme, and the ceramic porous substrate has a longitudinal through-hole structure that penetrates the upper and lower surfaces (liquid absorption surface and atomization surface) of the ceramic substrate in a vertical direction. Since the fibers of the organic template in the above scheme can be in a straight-through state, the through-hole structure can be an ordered straight-through hole.

[0125] In some other optional embodiments, the ordered straight through holes or ordered curved through holes can also be prepared on a dense substrate by laser drilling or etching. The dense substrate can be a ceramic substrate or a glass substrate. The above preparation method is a prior art and will not be repeated here.

[0126] In summary, the pore structure with substantially the same extension direction of this pore structure is referred to as ordered pores in the present invention. The porous matrix of this porous structure includes ordered pores extending in the thickness direction, and also includes ordered pores extending in the direction parallel to the atomization surface. It is understood that in some other embodiments, only ordered pores extending in the thickness direction may be included. At the same time, since the ordered pores run through the entire porous matrix, and the through hole can be in a vertical or curved state, the present invention is also referred to as ordered straight through holes or ordered curved through holes. Therefore, in some embodiments, the pores of the porous matrix include ordered straight through holes or ordered curved through holes. Depending on the raw materials used, the material of the porous matrix can be ceramic and / or glass. In the present invention, the porous matrix with this structure is named as the second porous matrix.

[0127] Typically but not limiting, in some other optional embodiments, the method for preparing the porous matrix comprises the following steps: preparing the porous matrix by molding glass and fiber materials and pore-forming agent powders.

[0128] Generally, for five close packing modes of equal-diameter spheres: simple cubic close packing, coordination number 6, packing density 52.4%; orthogonal close packing, coordination number 8, packing density 60.5%; tetragonal close packing, coordination number 10, packing density 69.8%; face-centered cubic close packing and hexagonal close packing, coordination number 12, packing density 74.2%. In order to obtain the porous glass material constructed with multi-directional interconnected pores, the pore former is designed to be added according to the volume ratio of the close packing, that is, the volume of the pore former accounts for 60-75% of the total material volume, preferably, the volume of the pore former accounts for 70-75% of the total volume.

[0129] Glass powder acts as a bonding skeleton. Fine glass powder can be evenly dispersed throughout the system, making the porous glass pores more evenly distributed and well connected after sintering. At the same time, fine glass powder can shorten the sintering time and reduce glass flow at high temperatures, thereby increasing the uniformity of the overall material while improving efficiency. The fiber component in this case acts as a skeleton support. For the preparation of porous materials with a pore size of 70-80 microns and a pore throat of 30-40 microns, the preferred supporting fiber skeleton is 70-150 microns. Generally, small-sized fibers or ceramic particles do not affect the overall scaffolding structure. After sintering, small-sized fibers or ceramic particles are wrapped by glass powder and aggregated at the fiber bonding point (pore-forming agent gap) to form support endpoints.

[0130] The porous glass includes a skeleton and multi-directional interconnected holes, wherein the skeleton includes a fiber skeleton with a scaffolding structure and a glass covering bonding layer with a bonding and stabilizing effect; the fiber skeleton has a length of 70-150 microns, a skeleton diameter of 15-45 microns, and a weight percentage range of 12-45%; the fiber skeleton material is a high-temperature resistant ceramic fiber material, including alumina, mullite, zirconia, etc., the fiber diameter is 10-40 microns, and the length is 10-150 microns, wherein the effective fiber length of the scaffolding structure is 70-150 microns; the glass covering bonding layer includes glass material and fibers or ceramic powders without a scaffolding structure, and the weight percentage range is 55-88%.

[0131] Optionally, the method for preparing the porous glass material generally includes: mixing glass powder, fiber components, and pore-forming agents to prepare a green body, debinding, sintering, and the like.

[0132] Optionally, the fiber component has a diameter of 3-30 μm and a length of 20-500 μm;

[0133] Optionally, the fiber component has a diameter of 10-25 μm and a length of 20-150 μm.

[0134] Optionally, the aspect ratio of the fiber component is 1-10, and optionally, the aspect ratio of the fiber with a length of 50-150 μm is 2-5;

[0135] And / or, in the fiber component, fibers with a fiber length of more than 50 μm account for 25%, optionally, account for more than 40%; further optionally, account for 40-100%.

[0136] Based on the total weight of the glass powder and the fiber component, the glass powder accounts for 40-62%, and the fiber component accounts for 38-60%;

[0137] And / or, the amount of the pore former used is 0.3-2.5 times the total mass of the glass powder and fiber components.

[0138] Select any one of the following processes: tape casting, injection molding, dry pressing, and gel casting to prepare the green body;

[0139] The above processes for preparing green bodies are all known in the art, and corresponding processing aids can be added and used according to different selected processes. Typically, but not limitingly, the steps of the injection molding process are roughly as follows: the mixed materials and injection molding additives (paraffin, polyethylene and dispersant, etc.) are mixed at high temperature in an internal mixer until they are uniform, and then a green body of a specified shape is prepared by injection molding. The amount of the injection molding additive is 5-50% of the total mass of the mixed materials, and the dispersing aid is selected from dibutyl phthalate.

[0140] And / or, the debinding temperature is 200-800°C, and the debinding time is 5-50h; optionally, the debinding temperature is 200-350°C.

[0141] And / or, the sintering temperature is 900-1250° C. or 1180-1320° C., and the sintering time is 10-180 min.

[0142] Optionally, the method for preparing the porous glass satisfies at least one of the following (1)-(5):

[0143] (1) The softening temperature of the glass powder is 600-1200°C; the softening point of the selected fiber raw material is above the sintering temperature in the preparation method and can play a skeleton role;

[0144] (2) The particle size of the glass powder is less than 10 μm, and optionally, the particle size is less than 3000 mesh;

[0145] (3) The fiber component is at least one of silicon carbide fiber, silicon nitride fiber, aluminum silicate fiber, quartz fiber, mullite fiber, alumina fiber, hydroxyapatite fiber, and zirconium oxide fiber;

[0146] (4) The pore-forming agent material is one or a mixture of materials such as carbon powder, polystyrene, polymethyl methacrylate, polylactic acid, polyvinyl alcohol, polyethylene terephthalate, engineering plastics, starch, cellulose, sawdust, graphite powder, etc. that can be decomposed, volatilized or burned by high temperature;

[0147] (5) The particle size of the pore former is 10-300 μm, and optionally, the average particle size of the pore former is 80 μm. A porous glass material with better connectivity can be obtained by adjusting the addition ratio of pore formers with different diameters.

[0148] In order to obtain the porous glass with special pore structure, the glass raw materials and fiber materials are pretreated as follows:

[0149] (1) The particle size of the glass powder raw material is less than 10 microns, and preferably glass powder with a mesh size of less than 3000 is used. In order to obtain glass powder with uniform particle size, commercially available glass powder can be milled for 3-5 hours using ethanol as solvent and a high-energy planetary ball mill at a speed of 200-500 r / min, and then dried and sieved before use.

[0150] (2) The fiber can be mullite fiber, zirconia fiber or alumina fiber and other high temperature resistant fibers. In this case, mullite fiber is preferred, with a fiber diameter of 10-25 microns, a length of less than 100 microns, and a fiber aspect ratio of 1-10. Generally, commercially available 2-5 mm short-cut fibers are first crushed to less than 0.5 mm by a crusher, and then ethanol is used as a solvent and stearic acid is used as a grinding aid. High-energy planetary ball milling is performed for 2-8 hours at a ball milling speed of 100-400 r / min. Preferably, ball milling is performed at 300 r / min for 6 hours. The ball-milled fibers are washed with ethanol, dried and passed through a 100-mesh sieve to obtain the target fibers.

[0151] Optionally, the porous glass with multi-directional interconnected pores is prepared by injection molding, and the preparation method is as follows:

[0152] Glass, fiber, and pore former are mixed in a certain proportion and mixed with a three-dimensional mixer for 2 hours until uniform. The pore former is a spherical pore former with a particle size of 10-300 microns. Preferably, the diameter of the pore former is 80 microns, or the diameter of the pore former is 50 microns. The mixed material and injection molding additives (paraffin, polyethylene and dispersant) are mixed at high temperature in a mixer until uniform, and then prepared into a green body of a specified shape by injection molding. Heat to 200°C in 200 minutes, and then heat to 500°C at 0.5°C per minute, wherein the insulation time is set at 240°C, 280°C, 300°C, and 350°C for 2 hours, and then heat to 1180°C-1320°C at 5°C per minute, keep warm for 30 minutes, and cool naturally to room temperature. In general, a better debinding process can be obtained according to the thermogravimetric curve of the pore former.

[0153] Alternatively, the porous glass with multi-directional interconnected pores can be prepared by directly densely packing hollow glass microspheres and then sintering. Generally, the particle size of the selected hollow glass microspheres is 50-120 microns, preferably, the particle size of the hollow glass microspheres is 80-100 microns. Generally, the porous matrix can be prepared by gel injection molding, first heating the hollow glass microspheres to 80°C, then adding them to a sol solution at 80°C, stirring, degassing, and injecting them into a mold at a pressure of 5MPa, and cooling them into a gel blank, drying the blank at 50°C, and then sintering at 1000°C for 30 minutes, and obtaining a porous glass matrix after natural cooling.

[0154] A porous glass with multi-directional connected pores (referred to as the third porous matrix) is prepared by the above preparation method, comprising a skeleton and multi-directional connected pores, wherein the multi-directional connected pores are spherical pores connected to at least 6 pores around them. As described above, the pores of the porous matrix are mainly disordered pores. The porous matrix mainly contains glass phase components.

[0155] In some optional embodiments, the heating element is a metal mesh or a metal sheet. It is understood that the metal mesh or the metal sheet itself is a dense structure. The transition layer has a certain bonding effect when sintered at high temperature, and has a good bonding effect with the dense structure of the metal mesh or metal sheet, thereby improving the bonding strength of the heating element, the transition layer and the porous matrix as a whole, preventing warping, increasing the service life of the atomizer core, and solving the problem of easy dry burning.

[0156] In some optional embodiments, at least part of the surface of the heating element has a micro-nano structure. The micro-nano structure is a microscopic structure of a certain size arranged on the surface of the heating element, and the size range is usually below the micron level. Providing a micro-nano structure on the contact surface with the transition layer can improve the bonding performance between the transition layer and the heating element; providing a micro-nano structure on the atomization surface of the heating element can enhance the inlet taste of the atomized medium. The formation method of the micro-nano structure can be selected from at least one of sandblasting, laser etching, and chemical corrosion. Preferably, the roughness (Ra) of the surface of the heating element with the micro-nano structure is 100-300nm.

[0157] In some optional embodiments, the material of the heating element is selected from at least one of an iron-based alloy material and a nickel-based alloy material; further, the heating element is selected from at least one of stainless steel and iron-chromium-aluminum.

[0158] In some optional embodiments, the thickness of the heating element is 20-200 μm; preferably, the thickness of the heating element is 50-120 μm. For example, the thickness of the heating element can be 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 112 μm, 115 μm, 120 μm.

[0159] For example, the present invention can select stainless steel with low resistivity, generally with a thickness of 20-200 μm and a line width of 60-80 μm, or can select iron-chromium-aluminum, with a thickness of 50-120 μm and a line width of 60-100 μm.

[0160] In some optional embodiments, the resistance of the heating element is 0.5-1.5Ω. For example, the resistance of the heating element can be selected to be 0.5Ω, 0.6Ω, 0.7Ω, 0.8Ω, 0.9Ω, 1Ω, 1.1Ω, 1.2Ω, 1.3Ω, 1.4Ω, or 1.5Ω.

[0161] In some optional embodiments, the shape of the heating element is rhombus or honeycomb. Figure 3 , Figure 4 As shown, the heating element can be composed of a plurality of rhombuses or a plurality of honeycombs. Further, the heating element is composed of 1-15 holes of rhombuses or 1-15 holes of honeycombs.

[0162] In some optional embodiments, the present invention provides a method for preparing the above-mentioned atomizer core without specific limitation, and can be selected to include the following steps:

[0163] The transition layer slurry is coated on the heating element, and then the heating element coated with the transition layer slurry is attached to the porous substrate, sintered and solidified, and cooled to obtain the atomization core.

[0164] Optionally, the method includes the following steps: coating one side of the heating element with the transition layer slurry, attaching the side of the heating element coated with the transition layer slurry to a porous substrate, sintering and solidifying, and cooling to obtain the atomizing core; the transition layer in the atomizing core is bonded between the porous substrate and the heating element.

[0165] Alternatively, the method includes the following steps: coating one side of the porous substrate with the transition layer slurry, which can be coated according to the shape of the heating element through a screen template; then attaching the heating element to the area of ​​the porous substrate coated with the transition layer slurry, sintering and solidifying, and cooling to obtain the atomizer core; the transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0166] In an optional embodiment, the sintering and curing temperature is 800-1000° C., the sintering and curing time is 8-12 min; the heating rate of sintering and curing is 8-30° C. / min; and the cooling is natural cooling to room temperature.

[0167] In an optional embodiment, the thickness of the transition layer slurry is 20-100 μm, wherein the transition layer slurry includes organic carriers such as solvents and binders in addition to raw material powders such as glass powder. The solvent can usually be water-based or alcohol-based (such as pine alcohol), and the binder can be cellulose such as methyl cellulose and ethyl cellulose.

[0168] In an optional embodiment, the mass ratio of the raw material powder, the solvent and the binder in the transition layer slurry is (70-200): (50-150): (20-80).

[0169] In some optional embodiments, the method for preparing the atomizer core may further include applying pressure to an external template during sintering and solidification.

[0170] The present invention also provides an atomizer, comprising the above-mentioned atomizer core. The atomizer further comprises a liquid storage tank for storing liquid atomizing medium and directing the atomizing medium to the atomizing core. The atomizing core can atomize the atomizing medium to generate aerosol in an energized mode.

[0171] The present invention also provides an electronic atomization device, comprising the above-mentioned atomizer and a power supply assembly, wherein the power supply assembly is used to supply power to the atomizer in a preset manner.

[0172] In the following embodiments of the present invention, the porous substrate and its preparation method are as follows:

[0173] The first porous matrix comprises a plurality of glass ceramic bubbles; wherein adjacent glass ceramic bubbles are directly bonded to each other by sintering; at least some of the glass ceramic bubbles have openings; the cavities within the glass ceramic bubbles having openings are interconnected through the openings to form pores, wherein the pores extend through the porous glass ceramic matrix and reach the surface of the porous glass ceramic matrix.

[0174] The preparation method of the first porous substrate comprises the following steps:

[0175] 1) 100 g of glass bubbles (the raw material glass bubbles are soda-lime silicate glass, the particle size parameters are: D10=18.61 μm, D50=39.38 μm, D90=69.47 μm, the porosity of the glass bubble monomer is 84.8%; the main components are Si: 41.647 wt%, O: 49.375 wt%, Na: 3.778 wt%, Ca: 4.619 wt%, Mg: 0.201 wt%, Al: 0.379 wt%), 25 g of hydroxyethyl cellulose, 2.5 g of sodium stearate, and 48 g of water are mixed and extruded to obtain a green body, and the molding pressure is 23 bar;

[0176] 2) The green body in step 1) is subjected to a first sintering, a second sintering and a third sintering to obtain a porous glass-ceramic matrix, wherein the first sintering temperature is 220°C, the first sintering time is 2 hours, the second sintering temperature is 600°C, the second sintering time is 2 hours, the third sintering temperature is 1200°C, the third sintering time is 1 hour, and finally, the green body is naturally cooled in the furnace to obtain a porous glass-ceramic matrix.

[0177] The porosity of the porous matrix was tested by mercury intrusion method and was 62.01%, with an average pore size of 18.4 μm.

[0178] The second porous matrix has a longitudinal through-hole structure that vertically penetrates the upper and lower surfaces (liquid absorption surface and atomization surface) of the ceramic matrix and a transverse curved through-hole structure connected to the longitudinal through-hole.

[0179] The preparation method of the second porous matrix comprises the following steps:

[0180] 1) Using a plain weaving method, nylon threads are alternately woven into a wire mesh by warp and weft, wherein the diameter of the warp of the wire mesh is 40 microns, the spacing between adjacent warps is 80 microns, the diameter of the weft is 40 microns, and the spacing between adjacent wefts is 80 microns. The wire mesh is fixed by a metal outer frame, and then stacked and fixed by a clamp to form a three-dimensional organic template, the number of stacked layers is 80, and the thickness after stacking is 4 mm;

[0181] 2) 70g of silicon dioxide powder, 10g of sintering aid potassium feldspar, 4g of acrylamide, 1g of N,N'-methylenebisacrylamide, and 15g of water were mixed, and the pH was adjusted to 8.5 with 15% ammonia water, and the ceramic slurry was obtained by ball milling at a speed of 50rpm and a ball milling time of 24h; 1g of ammonium persulfate and 0.5g of tetramethylethylenediamine were added to the ceramic slurry, and the mixture was filled into the three-dimensional organic template after being stirred evenly, dried, degreased, and sintered to form a three-dimensional organic template, and the three-dimensional organic template was ablated to form three-dimensional pores in the matrix, wherein the drying environment humidity was 50%, the drying temperature was 45°C, the drying time was 72h, the degreasing temperature was 500°C, the degreasing time was 1800min, the sintering temperature was 1150°C, and the sintering time was 1200min, and a porous ceramic matrix was obtained. The porosity of the porous matrix was 58% and the average pore size was 40 microns when the mercury injection method was used to test the porous matrix.

[0182] The third porous matrix includes a skeleton and multi-directional interconnected holes, wherein the multi-directional interconnected holes are spherical holes connected with at least six holes around them.

[0183] The preparation method of the third porous matrix comprises the following steps:

[0184] Using ethanol as solvent, the glass powder is ball-milled in a planetary ball mill at a speed of 300 r / min for 3 hours, dried and sieved to obtain glass powder with a particle size of less than 5 microns; the crushed mullite chopped fibers are planetarily ball-milled for 6 hours at a speed of 300 r / min using stearic acid as a grinding aid and ethanol as a solvent, washed with ethanol, dried, and sieved with 100 mesh to obtain fiber raw materials. 13 volumes of glass powder (density 2.5 g / mL), 12 volumes of fiber (density 2.8 g / mL, the same below), and 75 volumes of PMMA (80 microns) pore-forming agent were mixed in a three-dimensional mixer for 2 hours. The mixed materials were added to an internal mixer, and 20% paraffin, 5% polyethylene, and 5% dispersing aid (dibutyl phthalate) were added. The mixture was mixed at 180°C for 2 hours, and then prepared into a green body by an injection molding machine. The microscopic morphology is as follows: in one plane, the pore-forming agent is closely stacked with the surrounding 6 pore-forming agents, and the pore-forming agent has a face-centered close-packed or hexagonal close-packed tendency. The temperature was raised to 200°C in 200 minutes, and then raised to 500°C at 0.5°C per minute, wherein the holding time was set at 240°C, 280°C, 300°C, and 350°C for 2 hours, and then raised to 1180°C at 5°C per minute, and kept for 30 minutes, and naturally cooled to room temperature to obtain a porous glass material with a fiber volume content of 48%. The microscopic morphology of the porous glass matrix after sintering: the densely packed pore-forming agent was sintered to leave a pore structure, and in the same plane, the pores generated by the pore-forming agent were interconnected with about 6 surrounding pores. The porosity of the porous matrix was 72.0% and the average pore size was 40 microns when tested by mercury intrusion.

[0185] Example 1

[0186] This embodiment provides an atomizer core, comprising the following steps:

[0187] The transition layer slurry is coated on one side of the 8-hole diamond-shaped 430 stainless steel mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The heating element thickness is 50μm and the resistance is 0.7Ω. Then, one side of the heating element coated with the transition layer slurry is attached to the first porous substrate, heated to 1000℃ and sintered for 10min, with a heating rate of 10℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0188] The structural characteristics of the atomizer core prepared in this embodiment are as follows: Figure 1 , Figure 2 , Figure 4 and Figure 5 As shown. Among them, Figure 1 This is a schematic diagram of the cross section of the atomizer core. Figure 2This is a cross-sectional SEM image of the atomizer core; as shown in the figure, the transition layer is bonded between the porous matrix and the heating element, and the transition layer is partially filled into the porous matrix. Figure 4 and Figure 5 As shown in FIG. 1 , the transition layer is filled in the area where the heating element contacts the porous substrate. The area on the atomized surface of the porous substrate that is not in contact with the heating element has a complete pore structure and is not filled and covered by the transition layer. The ratio of the area of ​​the porous substrate filled with the transition layer to the area of ​​the porous substrate covered by the heating element is approximately 1:1. Figure 2 As shown, the transition layer fills part of the pores of the porous matrix to form an embedded structure, and the transition layer structure is dense. Furthermore, the maximum thickness of the transition layer is about 140 μm, and the minimum thickness is about 20 μm.

[0189] Example 2

[0190] This embodiment provides an atomizer core, comprising the following steps:

[0191] The transition layer slurry is coated on one side of the 8-hole rhombus iron-chromium-aluminum mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 200:150:80. The heating element thickness is 100μm and the resistance is 1.1Ω. Then, one side of the heating element coated with the transition layer slurry is attached to the first porous substrate, heated to 1000℃ and sintered for 10min, with a heating rate of 8℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0192] The atomizer core prepared in this embodiment has the same or similar structural features as those in Embodiment 1, which will not be described in detail here. Different from the above-mentioned embodiment, the maximum thickness of the transition layer in this embodiment is about 70 μm, and the minimum thickness is about 30 μm.

[0193] Example 3

[0194] This embodiment provides an atomizer core, comprising the following steps:

[0195] The transition layer slurry is coated on one side of the 8-hole diamond-shaped 430 stainless steel sheet heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The thickness of the heating element is 50μm, the resistance is 0.7Ω, and the double-sided sandblasting forms a micro-nano structure to change the surface roughness. Then, one side of the heating element coated with the transition layer slurry is attached to the first porous substrate, heated to 1000℃ and sintered for 12min, the heating rate is 30℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0196] The atomizer core prepared in this embodiment has the same or similar structural features as those in Embodiment 1, which will not be described in detail here. Different from the above-mentioned embodiment, the surface of the heating element in this embodiment has a micro-nano structure with a roughness of Ra=100-300nm.

[0197] Example 4

[0198] This embodiment provides an atomizer core, comprising the following steps:

[0199] The transition layer slurry is coated on one side of the 8-hole rhombus iron-chromium-aluminum mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The thickness of the heating element is 100μm, the resistance is 1.1Ω, and the double-sided sandblasting forms a micro-nano structure to change the surface roughness. Then, one side of the heating element coated with the transition layer slurry is attached to the first porous substrate, heated to 1000℃ and sintered and cured for 10min, the heating rate is 8℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0200] The atomizer core prepared in this embodiment has similar structural features to those in Embodiment 3, and will not be described in detail here.

[0201] Example 5

[0202] This embodiment provides an atomizer core, comprising the following steps:

[0203] The transition layer slurry is coated on one side of the 8-hole diamond-shaped 430 stainless steel mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The thickness of the heating element is 50μm, the resistance is 0.7Ω, and the double-sided sandblasting forms a micro-nano structure to change the surface roughness. Then, one side of the heating element coated with the transition layer slurry is attached to the first porous substrate, heated to 1000℃ and sintered for 10min, the heating rate is 8℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0204] The atomizer core prepared in this embodiment has similar structural features to those in Embodiment 3, and will not be described in detail here.

[0205] Example 6

[0206] This embodiment provides an atomizer core, comprising the following steps:

[0207] The transition layer slurry is coated on one side of the 8-hole diamond-shaped 316L stainless steel mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The thickness of the heating element is 50μm, the resistance is 0.8Ω, and the double-sided sandblasting forms a micro-nano structure to change the surface roughness. Then, one side of the heating element coated with the transition layer slurry is attached to the first porous substrate, heated to 1000℃ and sintered for 10min, the heating rate is 8℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0208] The atomizer core prepared in this embodiment has similar structural features to those in Embodiment 3, and will not be described in detail here.

[0209] Example 7

[0210] This embodiment provides an atomizer core, comprising the following steps:

[0211] The transition layer slurry is coated on one side of the 8-hole diamond-shaped 430 stainless steel mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The heating element thickness is 50μm and the resistance is 0.7Ω. Then, one side of the heating element coated with the transition layer slurry is attached to the third porous substrate, heated to 1000℃ and sintered for 12min, with a heating rate of 30℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0212] The atomizer core prepared in this embodiment has similar structural features to those of the aforementioned embodiment 1, and will not be described in detail here.

[0213] Example 8

[0214] This embodiment provides an atomizer core, comprising the following steps:

[0215] The transition layer slurry is coated on one side of the 8-hole diamond-shaped 430 stainless steel mesh heating element, and the slurry thickness is 50μm, wherein the transition layer slurry composition ratio includes glass powder, pine alcohol and methyl cellulose in a mass ratio of 100:80:20. The heating element thickness is 50μm and the resistance is 0.7Ω. Then, one side of the heating element coated with the transition layer slurry is attached to the second porous substrate, heated to 1000℃ and sintered for 12min, with a heating rate of 30℃ / min, and then naturally cooled to room temperature to obtain the atomizer core. The transition layer in the atomizer core is bonded between the porous substrate and the heating element.

[0216] The atomizer core prepared in this embodiment has similar structural features to those in Embodiment 1, which will not be described in detail here. Different from the above-mentioned embodiment, the second porous matrix in this embodiment has ordered pores, so the penetration depth of the transition layer is relatively uniform.

[0217] Test Example 1

[0218] The atomizer cores of Examples 1-6 of the present invention were tested for dry burning life and wet burning life. Dry burning life refers to: when the heating element is heated in the bare chip, the test conditions of pumping for 3s and stopping for 8s are used under the power (7.5-8w), and a cycle test is performed to judge the bare chip condition of the heating element. It can be used to judge the bonding strength performance. If the strength is insufficient, the heating element will be warped off the substrate or broken during the test. Abnormal phenomena such as. Wet burning life refers to: when the heating element is normally loaded into the atomizer and inhaled, the test conditions of pumping for 3s and stopping for 27s are used under the power (7.5-8w), and a cycle test is performed to judge the heating element in the atomizer. It can be used to judge the bonding strength performance. If the strength is insufficient, the heating element will be warped off the substrate, broken or failed during the test. When judging the failure situation, one of the following situations is met: 1. The resistance of the atomizer core changes significantly abnormally (such as: the resistance caused by the breakage and shedding of the heating element increases significantly by more than 20% of the original resistance); 2. The amount of mist output is less than half of the initial atomization amount. The test conditions and test results of this test example are shown in Table 1.

[0219] Table 1

[0220]

[0221] As shown in Table 1, in the actual use environment of thermal shock in the atomizer core, since most of the heating element is in close contact with the porous matrix, its deformation is constrained. Under the condition of thermal shock, the deformation of each part of the heating element is relatively consistent and constrained, and it is not easy to cause warping, breakage, etc., thereby extending the service life of the atomizer core.

[0222] Test Example 2

[0223] The temperature field of multiple samples of the atomizer core prepared in Examples 1 and 2 of the present invention was tested. The temperature field of the atomizer core was measured by using an infrared thermometer to obtain the distribution of the temperature field, and then the distribution of the temperature field was statistically analyzed. The test results are shown in Table 2 and Figure 6 , Figure 7 As shown. The highest temperature of the heating element is about 292℃; Figure 7 As shown, these are multiple different samples prepared in Example 1. The temperature field distribution differences between the multiple different samples are small, and the product consistency is good.

[0224] Table 2 Temperature field test

[0225]

[0226]

[0227] Test Example 3

[0228] The atomizers corresponding to the atomizer cores of Example 1, Example 7, and Example 8 were tested for smoke volume and noise. Smoke volume attenuation refers to the difference between the minimum smoke volume and the maximum smoke volume within the preset life cycle; Smoke volume attenuation = (maximum smoke volume - minimum smoke volume) / maximum smoke volume * 100%. Usually, the smoke volume shows a decay trend, that is, the maximum smoke volume is the initial smoke volume, and the minimum smoke volume is the final smoke volume. Among them, the test condition is a constant power of 8W, and the test atomization matrix is ​​a commercially available tobacco-flavored liquid atomization medium (Crane Dance Tower). The test results are shown in Table 3.

[0229] Table 3

[0230] Test indicators Example 7 Example 8 Example 1 Finished product smoke content (mg / puff) 8.95 8.43 8.85 Finished product wet-fired life (mouth) ≥500 mouths ≥500 mouths ≥500 mouths Smoke volume attenuation 15.3% 12.9% 5.3% noise <40dB <40dB <40dB

[0231] Combined with the results of test examples 2 and 3, the atomizer core prepared in the embodiment of the present invention also has the characteristics of good consistency and long service life. Among them, the technical effect of good consistency is reflected in the following aspects: first, the consistency between different samples in the same batch is good; Figure 6 As shown, the difference in temperature curves between the three samples in Example 1 (respectively denoted as V7-1, V7-2, and V7-3) is extremely small. The inventors analyzed that, through the provision of the transition layer, the consistency of the interval between the heating element and the porous matrix is ​​improved, the influence of the deformation of the porous matrix and the heating element is reduced, and the product consistency between different samples is improved. Second, the consistency of the same sample in the life cycle is good, which is reflected in the small smoke attenuation and long life. As shown in Table 3, in a usage cycle of ≥500 puffs, at 500 puffs, the attenuation of Example 7 was about 15.3%, and the attenuation of Example 1 was only 5.3%, which is much lower than the attenuation in the prior art. At the same time, the suction noise is also all less than 40 decibels; usually, the size of the suction noise can comprehensively reflect the liquid supply capacity and atomization effect of the atomizer core from the side. Excessive noise usually reflects problems such as local dry burning of the atomizer core and excessively thick oil film. Combined with Figure 7 As shown, the temperature field distribution consistency between different samples in Example 1 is good, and at the same time the temperature field distribution on the atomizing surface of the atomizing core is improved, local high temperature is avoided, and the occurrence of dry burning is reduced.

[0232] Combined with the above test results and analysis, the present invention has made comprehensive improvements and upgrades in at least multiple dimensions such as the temperature field distribution of the atomizer core, the consistency of the atomizer core, the service life, the mechanical properties, and dry burning, thereby improving the performance of the atomizer core and solving the problems existing in the prior art.

[0233] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An atomizer core, characterized in that: The atomizing core comprises a porous matrix, a heating element, and a transition layer bonded between the porous matrix and the heating element; The transition layer contains inorganic material components.

2. The atomizer core according to claim 1, characterized in that: The transition layer contains a glass phase component; and / or, the porous matrix contains glass phase components and / or ceramic phase components; Preferably, the softening point temperature of the glass in the transition layer is 400°C-1100°C.

3. The atomizer core according to claim 1 or 2, characterized in that: The content of inorganic material components in the transition layer is greater than 80wt%; Preferably, the content of inorganic material components in the transition layer is greater than 90wt%; Preferably, the content of the inorganic material component in the transition layer is 100 wt %.

4. The atomizer core according to any one of claims 1 to 3, characterized in that: The transition layer at least partially fills and / or covers the porous matrix; Preferably, the transition layer at least partially fills and / or covers the area where the heating element contacts the porous matrix; Preferably, the area on the porous substrate that is not in contact with the heating element is at least partially not filled and / or covered by the transition layer.

5. The atomizer core according to any one of claims 1 to 4, characterized in that: The transition layer fills part of the pores of the porous matrix to form an embedded structure; And / or, the transition layer is a dense structure.

6. The atomizer core according to any one of claims 1 to 5, characterized in that: The thickness of the transition layer is 20-200 μm; Preferably, the transition layer has a thickness of 100-160 μm.

7. The atomizer core according to any one of claims 1 to 6, characterized in that: The composition of the transition layer includes aluminosilicate glass and / or barium silicate glass; And / or, the composition of the porous matrix includes soda-lime silicate glass and / or borosilicate glass.

8. The atomizer core according to any one of claims 1 to 7, characterized in that: The porosity of the porous matrix is ​​20%-90%; Preferably, the porosity of the porous matrix is ​​40-80%.

9. The atomizer core according to any one of claims 1 to 8, characterized in that: The average pore size of the porous matrix is ​​10-300 μm; Preferably, the average pore size of the porous matrix is ​​15-60 μm; Preferably, the average pore size of the porous matrix is ​​20-50 μm.

10. The atomizer core according to any one of claims 1 to 9, characterized in that: The pores of the porous matrix include at least one of ordered straight through pores, ordered curved through pores or disordered pores.

11. The atomizer core according to any one of claims 1 to 10, characterized in that: The heating element is a metal mesh or a metal sheet; And / or, the material of the heating element is selected from at least one of an iron-based alloy material and a nickel-based alloy material; Preferably, the heating element is selected from at least one of stainless steel and iron-chromium-aluminum.

12. The atomizer core according to any one of claims 1 to 11, characterized in that: The shape of the heating element is rhombus or honeycomb.

13. The atomizer core according to any one of claims 1 to 12, characterized in that: The thickness of the heating element is 20-200 μm; Preferably, the heating element has a thickness of 50-120 μm.

14. The atomizer core according to any one of claims 1 to 13, characterized in that: At least part of the surface of the heating element has a micro-nano structure; Preferably, the surface roughness Ra of the heating element with micro-nano structure is 100-300nm.

15. The atomizer core according to any one of claims 1 to 14, characterized in that: The ratio of the area of ​​the porous matrix filled and / or covered by the transition layer to the area of ​​the porous matrix covered by the heating element is (0.8-1.2):1; Preferably, the ratio of the area of ​​the porous matrix filled and / or covered by the transition layer to the area of ​​the porous matrix covered by the heating element is 1:

1.

16. An atomizer, characterized in that: Comprising the atomizer core as described in any one of claims 1-15.

17. An electronic atomization device, characterized in that: It comprises the atomizer and power supply assembly as claimed in claim 16.

Citation Information

Cited By

  • Ceramic matrix as well as preparation method and application thereof

    CN118666593A

  • Atomization core, atomizer, and electronic atomization device

    EP4762959A1